2018
DOI: 10.1186/s12931-018-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the purinergic pathway involved in the pathology of COPD? Decreased lung CD39 expression at initial stages of COPD

Abstract: BackgroundExtracellular adenosine triphosphate (ATP) is up-regulated in the airways of patients with chronic obstructive pulmonary disease (COPD), resulting in increased inflammation, bronchoconstriction, and cough. Although extracellular ATP levels are tightly controlled by nucleoside triphosphate diphosphohydrolase-1 (NTPDase1; also known as CD39) in the lungs, the role of CD39 in the pathology of COPD is unknown. We hypothesized that alterations in the expression and activity of CD39 could be part of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…CD39 converts ATP and ADP to AMP. Correlating with increased ATP levels in the airways of COPD smokers, there was a significant decrease in CD39 gene and protein expression and ATPase activity in lung tissue acquired from COPD patients when compared with non-obstructive smokers and never-smokers (113). CD39 is decreased on T-cells in acute exacerbation of COPD (AECOPD) patients when compared to stable COPD.…”
Section: Purinergic Signaling In Chronic Pulmonary Inflammationmentioning
confidence: 99%
“…CD39 converts ATP and ADP to AMP. Correlating with increased ATP levels in the airways of COPD smokers, there was a significant decrease in CD39 gene and protein expression and ATPase activity in lung tissue acquired from COPD patients when compared with non-obstructive smokers and never-smokers (113). CD39 is decreased on T-cells in acute exacerbation of COPD (AECOPD) patients when compared to stable COPD.…”
Section: Purinergic Signaling In Chronic Pulmonary Inflammationmentioning
confidence: 99%
“…Although these findings hint that adenosine receptors may modulate the course of COPD, further studies will be necessary to precisely delineate the role of the various adenosine receptors in regulating the course of COPD in patients. Aliagas et al (2018) found decreased CD39 gene and protein expression as well as activity in the lungs of COPD patients in comparison with controls. This decrease in CD39 correlated with higher systemic inflammation and intimal thickening of muscular pulmonary arteries in the COPD group (Aliagas et al, 2018).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 77%
“…Aliagas et al (2018) found decreased CD39 gene and protein expression as well as activity in the lungs of COPD patients in comparison with controls. This decrease in CD39 correlated with higher systemic inflammation and intimal thickening of muscular pulmonary arteries in the COPD group (Aliagas et al, 2018). Immunohistochemical analysis showed that CD39 was downregulated mainly in lung parenchyma, in epithelial bronchial cells, and in the endothelial cells of pulmonary muscular arteries (Aliagas et al, 2018).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 77%
See 1 more Smart Citation
“…Since our earlier work revealed a pathogenic role of the CD73/Adodependent arm of purinergic signaling in radiation-induced lung fibrosis (49,50), genetic loss of CD39 with assumed activation of the ATP-dependent proinflammatory arm of purinergic signaling and genetic loss of CD73 with assumed activation of the Ado-dependent anti-inflammatory, repair-promoting arm of purinergic signaling result in opposing outcomes in radiationinduced lung fibrosis. A pathology-promoting effect of low CD39 expression or high pulmonary ATP levels were already known for several lung pathologies, including pulmonary fibrosis (113)(114)(115). High extracellular ATP levels, for example, have been observed in the bronchoalveolar lavage fluid of patients with idiopathic pulmonary fibrosis, as well as in a murine model of bleomycin-induced lung fibrosis (116).…”
Section: The Role Of Cd39 Within Normal Lung Toxicitymentioning
confidence: 97%